Myotendinous junction plasticity in aged ovariectomized rats submitted to aquatic training - Rissatto Sierra, Luan [UNESP]; Fávaro, Gabriel [UNESP]; Cerri, Bruno Rubin [UNESP]; Rocha, Lara Caetano [UNESP]; de Yokomizo de Almeida, Sonia Regina; Watanabe, Ii-Sei; Ciena, Adriano Polican [UNESP] (Wiley, 2018)
The study aims to describe the tissue plasticity of MTJ through the morphological analysis of MTJ soleus in ovariectomized aged female Wistar rats submitted to aquatic training. Forty aged Wistar rats, 1 year and 2 months of age, were divided into four groups: sedentary (S), trained (T), ovariectomized (O), and trained/ovariectomized (OT). Employing the transmission electron microscopy, the ultrastructural and morphometric elements were revealed. In the S group, changes in morphological characteristics as a consequence of the aging process were seen, demonstrated by the conical shape of the muscle cell extremity, a large area with collagen deposit, and misalignment of sarcomeres in series. The T group presented ample adjustments when revealed the organization of MTJ, through the increase of the contact area and greater lengths of sarcoplasmatic invaginations and evaginations. The O group revealed extensive tissue disorganization with muscle atrophy, reduction of MTJ contact area, and consequently, changes in sarcoplasmatic invaginations and evaginations. The OT group demonstrated extensive remodeling with restructuring MTJ through the increase of tissue contact area, extensive organization, parallel arrangement, and increased length of sarcoplasmatic invaginations and evaginations. The distal sarcomeres presented higher lengths compared to the proximal sarcomeres in both the groups. We conclude that aquatic training was effective in the organization and structural remodeling of the myotendinous interface of ovariectomized aged rats. There was a greater area of contact, and consequently, greater resistance in the myotendinous interface promoting a lower predisposition to injuries.
Keywords: ageing; menopause; myotendinous junction; sarcomeres; swimming